2018
DOI: 10.1007/s00726-018-2575-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and characterization of a novel hemocyanin-derived antimicrobial peptide from shrimp Litopenaeus vannamei

Abstract: Hemocyanin, the multifunctional glycoprotein in the hemolymph of invertebrates, can generate various antimicrobial peptides (AMPs). Given the rising interest in the use of natural therapeutic agents such as AMPs, alternative and more efficient methods for their generation are being explored. In this work, free online software was first applied to predict the generation of antimicrobial peptides from the large subunit of Litopenaeus vannamei hemocyanin. Twenty potential antimicrobial peptides ranging from 1.5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Interestingly, other spots ranging from 20 to 60 kDa were also identified as HMC, which should be HMC fragments or modification isoforms ( Figure 1 ). In combination with previous reports that HMC possessed polymorphisms including SNPs ( 30 , 31 ) and alternative splicing variant ( 32 ) and could generate various antimicrobial peptides ( 7 , 12 , 17 , 18 , 51 , 52 ) with resistance to pathogens infection, all these results indicated that HMC varied at nucleotide and protein levels.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, other spots ranging from 20 to 60 kDa were also identified as HMC, which should be HMC fragments or modification isoforms ( Figure 1 ). In combination with previous reports that HMC possessed polymorphisms including SNPs ( 30 , 31 ) and alternative splicing variant ( 32 ) and could generate various antimicrobial peptides ( 7 , 12 , 17 , 18 , 51 , 52 ) with resistance to pathogens infection, all these results indicated that HMC varied at nucleotide and protein levels.…”
Section: Discussionsupporting
confidence: 79%
“…The shrimp L. vannamei is reported to generate different AMPs from hemocyanin, both naturally as part of the innate immune system and in response to specific pathogen challenge [13,14,46]. The antimicrobial activities of these shrimp hemocyanin-derived AMPs have been demonstrated [25]; however, their effect on cell proliferation and potential use as antiproliferative or antitumor agents has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pleurocidin family of AMPs (NRC-03 and NRC-07) derived from Atlantic flounder were found to kill breast carcinoma cells, including drug-resistant and slow-growing breast cancer cells [24]. Interestingly, our recent studies involving the screening of L. vannamei hemocyanin identified 20 potential AMPs ranging from 1.5 to 1.9 kDa [25]. While the antibacterial activities of these hemocyanin-derived peptides have been ascertained, whether or not these peptides also have anticancer effects is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The N. pompilius hemocyanin was obtained from our database, which has been published [ 22 ]. First, the antimicrobial peptide server (AntiBP: ; accessed on 19 April 2021) was utilized to search for potential AMPs in the N. pompilius hemocyanin sequence [ 51 ]. Then, the predicted AMPs were validated using the predict antimicrobial region within peptides tool from CAMP ( ; accessed on 19 April 2021) [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, the antimicrobial peptide server (AntiBP: https://webs.iiitd.edu. in/raghava/antibp/index.html/; accessed on 19 April 2021) was utilized to search for potential AMPs in the N. pompilius hemocyanin sequence [51]. Then, the predicted AMPs were validated using the predict antimicrobial region within peptides tool from CAMP (http://www.camp.bicnirrh.res.in/; accessed on 19 April 2021) [52].…”
Section: Prediction Of Amps From N Pompilius Hemocyaninmentioning
confidence: 99%